2012
DOI: 10.1128/iai.06054-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inflammatory Response on In Vivo Competition between Two Chlamydial Variants in the Guinea Pig Model of Inclusion Conjunctivitis

Abstract: In order to study the interaction of variants in in vivo infection, we employed an azithromycin-resistant mutant (AZ 2 ) and its wild-type parent (SP 6 ) in the guinea pig model of Chlamydia caviae conjunctival infection. When each strain was inoculated individually into conjunctiva, both attained the same level of growth, but AZ 2 elicited less pathology. However, when equal numbers of the two strains were inoculated together into the guinea pig conjunctiva, SP 6 produced a significantly greater number of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
(47 reference statements)
2
7
1
Order By: Relevance
“…Even though AZ2 has a lower burst size and a lower growth rate than SP6 in vitro, no difference in the course of the infection was seen between the two variants when assessed by two-factor (days and group) analysis of variance (ANOVA) with repeated measures (Fig. 1), similar to our observations in conjunctival infection (9). We had previously observed that AZ2 elicits a weaker inflammatory response than SP6 in the conjunctiva as a result of a decreased proinflammatory cytokine response in the AZ2-infected animals.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…Even though AZ2 has a lower burst size and a lower growth rate than SP6 in vitro, no difference in the course of the infection was seen between the two variants when assessed by two-factor (days and group) analysis of variance (ANOVA) with repeated measures (Fig. 1), similar to our observations in conjunctival infection (9). We had previously observed that AZ2 elicits a weaker inflammatory response than SP6 in the conjunctiva as a result of a decreased proinflammatory cytokine response in the AZ2-infected animals.…”
Section: Resultssupporting
confidence: 77%
“…Nevertheless, the outcome of our experiments marks a starting point for understanding how chlamydial variants compete within the context of an ascending genital tract infection. Similar to what we observed in the conjunctival model (9), the total number of chlamydiae in the cervix in the first 9 days postinfection in a mixed infection with SP6 and AZ2 was comparable to those in a monoinfection of each variant alone. However, of interest was our observation that SP6 outcompeted AZ2 in the mixture and by 9 days postinfection represented 92% of the total number of chlamydiae in the cervix.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations